International investment agreements : key issues (UN New YorkUS, 2004)
Provides a basic reference tool for use in the preparation of negotiations as well as for the development of model treaties. Analyzes issues that arise in negotiations and/or discussions of international investment agreements.
Keywords: INTERNATIONAL AGREEMENTS